Menggali Nilai-Nilai Karakter Melalui Pendidikan Al-Quran: Studi Kasus di TPA-TPA Terpilih. - Rahmawati, Putri Dwi; Khodijah, Siti; Ghofur, Abdul; Pratama, Rizky Ashil; Latifatunnisa, Fathia; Alfarras, Muhammad Dzikri (JOURNAL OF QUR'AN AND HADITH STUDIES, 2024)
This research aims to explore and elaborate on character values through Quranic education at selected TPAs (Islamic Education Centers) in Bekasi. This study employs a qualitative method with a descriptive-analytical case study approach. Data collection techniques include interviews, observations, and documentation. The results show that Quranic education at TPAs focuses not only on religious aspects but also on character development such as patience, honesty, and discipline. The approaches used include stories, educational games, and interactive activities to instill these values. Challenges in teaching include the diverse learning abilities of children and difficulties in memorization. This study emphasizes the importance of adaptive and responsive teaching methods to individual children's needs and support for educators in developing adequate skills and strategies.